'At the grass roots level it's about sitting down and talking': exploring quality improvement through case studies with high-improving Aboriginal and Torres Strait Islander primary healthcare services. Issue 5 (24th May 2019) - Larkins, Sarah; Carlisle, Karen; Turner, Nalita; Taylor, Judy; Copley, Kerry; Cooney, Sinon; Wright, Roderick; Matthews, Veronica; Thompson, Sandra; Bailie, Ross
Abstract : Objectives: Improving the quality of primary care is an important strategy to improve health outcomes. However, responses to continuous quality improvement (CQI) initiatives are variable, likely due in part to a mismatch between interventions and context. This project aimed to understand the successful implementation of CQI initiatives in Aboriginal and Torres Strait Islander health services in Australia through exploring the strategies used by 'high-improving' Indigenous primary healthcare (PHC) services. Design, settings and participants: This strengths-based participatory observational study used a multiple case study method with six Indigenous PHC services in northern Australia that had improved their performance in CQI audits. Interviews with healthcare providers, service users and managers (n=134), documentary review and non-participant observation were used to explore implementation of CQI and the enablers of quality improvement in these contexts. Results: Services approached the implementation of CQI differently according to their contexts. Common themes previously reported included CQI systems, teamwork, collaboration, a stable workforce and community engagement. Novel themes included embeddedness in the local historical and cultural contexts, two-way learning about CQI and the community 'driving' health improvement. These novel themes were implicit in the descriptions of stakeholders about why the services were improving. Embeddedness in the local historical and cultural context resulted in 'two-way' learning between communities and health system personnel. Conclusions: Practical interventions to strengthen responses to CQI in Indigenous PHC services require recruitment and support of an appropriate and well prepared workforce, training in leadership and joint decision-making, regional CQI collaboratives and workable mechanisms for genuine community engagement. A 'toolkit' of strategies for service support might address each of these components, although strategies need to be implemented through a two-way learning process and adapted to the historical and cultural community context. Such approaches have the potential to assist health service personnel strengthen the PHC provided to Indigenous communities.